Spectral theory of random Schrödinger operators : a genetic introduction - Lang, Reinhard (Lecture Notes in Mathematics, 1991)
The interplay between the spectral theory of Schr|dingeroperators and probabilistic considerations forms the maintheme of these notes, written for the non-specialist readerand intended to provide a brief and elementaryintroductionto this field.